Understanding the veterinary antibiotic flow in Malawi: Complexities, gaps and needs - Mhone, Amos L.; Muloi, Dishon M.; Moodley, Arshnee (Frontiers Media, 2024)
Introduction: Veterinary antibiotics are essential for maintaining animal health and welfare, however, small-scale farmers in Malawi face challenges in accessing them due to limited availability, affordability, and long distances to rural drug retailers.